Becoming an EC-4 teacher in Texas - Janice L. Nath (Wadsworth/Thomson Learning, 2003)
This is the only introduction to teaching text that is specifically built around the new Texas standards for teacher certification. Although there are many excellent introductory teaching texts, none of these are matched precisely to the Texas teacher certification standard. There are several practice TExES books, but they are short on theory. Nath and Cohen combine both, so not only will students pass the Texas certification text, they will also learn a great deal about good teaching practice